2016
DOI: 10.1212/wnl.0000000000002263
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis of cerebral white matter hyperintensities in patients with stroke

Abstract: Objective:For 3,670 stroke patients from the United Kingdom, United States, Australia, Belgium, and Italy, we performed a genome-wide meta-analysis of white matter hyperintensity volumes (WMHV) on data imputed to the 1000 Genomes reference dataset to provide insights into disease mechanisms.Methods:We first sought to identify genetic associations with white matter hyperintensities in a stroke population, and then examined whether genetic loci previously linked to WMHV in community populations are also associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 30 publications
3
90
0
Order By: Relevance
“…9 and 10). Prior studies have demonstrated that variants in this region are associated with white-matter hyperintensity (WMH) burden 17 , a brain magnetic resonance imaging marker of small-vessel disease (SVD).…”
Section: Resultsmentioning
confidence: 99%
“…9 and 10). Prior studies have demonstrated that variants in this region are associated with white-matter hyperintensity (WMH) burden 17 , a brain magnetic resonance imaging marker of small-vessel disease (SVD).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, genes at these loci are implicated in both AD and in (hemorrhagic) stroke [46]. Earlier findings have been replicated in independent population-based [47, 48] and clinical [49] samples. The CHARGE consortium also investigated whether genetic influences could be detected for the progression of white matter hyperintensities over time [50].…”
Section: Reviewmentioning
confidence: 99%
“…Jonathan Rosand, 5,6,7,48 Steven J. Kittner, 24 Braxton D. Mitchell, 61,62 Martin Dichgans, 2,63 Bradford B. Worrall, 64 and Hugh S. Markus 65 ; on behalf of the International Stroke Genetics Consortium Objective: Genome-wide association studies (GWAS) have been successful at identifying associations with stroke and stroke subtypes, but have not yet identified any associations solely with small vessel stroke (SVS). SVS comprises one quarter of all ischemic stroke and is a major manifestation of cerebral small vessel disease, the primary cause of vascular cognitive impairment.…”
mentioning
confidence: 99%